Prediction of postoperative pain after radical prostatectomy - Sjöström Björn; Nordberg Gunnar; Ene Kerstin; Bergh Ingrid (BMC, 2008)
Abstract Background There is a belief that the amount of pain perceived is merely directly proportional to the extent of injury. The intensity of postoperative pain is however influenced by multiple factors aside from the extent of trauma. The purpose of the study was to evaluate the relationship between preoperative factors that have been shown to predict postoperative pain and the self-reports of pain intensity in a population of 155 men undergoing radical prostatectomy (RP), and also to investigate if previous pain score could predict the subsequent pain score. Methods The correlation between potential pain predictors and the postoperative pain experiences during three postoperative days was tested (Pitmans' test). By use of a logistic regression analysis the probability that a Visual Analogue Scale (VAS) score at one occasion would exceed 30 mm or 70 mm was studied, depending on previous VAS score, age, depression and pain treatment method. Results Age was found to be a predictor of VAS > 30 mm, with younger patients at higher risk for pain, and preoperative depression predicted VAS > 70 mm. The probability that VAS would exceed 30 mm and 70 mm was predicted only by previous VAS value. Day two however, patients with epidural analgesia were at higher risk for experiencing pain than patients with intrathecal or systemic opioid analgesia. Conclusion The results show that it would be meaningful to identify RP patients at high risk for severe postoperative pain; i.e. younger and/or depressive patients who might benefit from a more aggressive therapy instituted in the very early postoperative period.